Effects of Expressive Writing on organizational variables in Palliative Care health Professionals: an explorative study - Cosentino, Chiara; Corte, Cristina; Fioresi, Elena; Molina Ojeda, Fiorella; Pastore, Sonia; Severgnini, Fabiana; Spacci, Alessio; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Healthcare professionals working in palliative care are exposed to emotionally intense conditions. Scientific literature suggests Expressive Writing as a valid tool for the adjustment to traumatic events. For health workers, EW represents an important support to prevent Compassion Fatigue and Burnout. As literature showed that Compassion Satisfaction, Group Cohesion and the Organizational Commitment are protective factors able to counter the onset of Compassion Fatigue and Burnout, the aim of this study is evaluating the effect of Expressive Writing protocol in Palliative Care workers on Compassion Satisfaction, Group Cohesion and Organizational Commitment. Methods: A quasi-experimental quantitative 2x2 prospective study was conducted with two groups and two measurements. 66 professionals were included. Outcome variables were measured using: Organizational Commitment Questionnaire, Compassion Satisfaction Rating Scale, ICONAS Questionnaire, Questionnaire for the evaluation of EW sessions. Results: The parametric analysis through Student t test did not show statistical significance within the experimental group and between the experimental and control groups. One significant difference in the pre-intervention assessment of Normative Commitment t (gl 64) = -2.008 for p< 0.05, higher in the control group, disappeared in the post intervention evaluation. An improvement trend in all variables within and between groups was present, with a positive assessment of utility from the participants. Conclusions: This intervention did not significantly impact outcome variables. It is however conceivable that by modifying the intervention methodology, it could prove effective. The positive evaluation by the operators, suggests to keep trying modelling a protocol tailored on Palliative Care professionals.